2014
DOI: 10.1371/journal.pone.0089637
|View full text |Cite
|
Sign up to set email alerts
|

Etiologies and Resistance Profiles of Bacterial Community-Acquired Pneumonia in Cambodian and Neighboring Countries’ Health Care Settings: A Systematic Review (1995 to 2012)

Abstract: ObjectivesCommunity-acquired pneumonia (CAP) is one of the most important causes of morbidity and mortality worldwide. Etiological data for Cambodia is scarce. We aimed to describe the main etiological agents causing CAP, and their resistance patterns in Cambodia and the greater Mekong region.MethodsA review of bacterial etiologies of CAP and antimicrobial resistance in Cambodia and neighboring countries was conducted via: (1) a systematic review of published literature in all NCBI databases using Pubmed, Goog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 55 publications
3
24
0
1
Order By: Relevance
“…38 This has changed the way local clinicians initiate their empiric treatment for patients admitted for severe CAP, with antibiotics deliberately chosen to cover Gram-negative organisms, melioidosis as well as Gram-positive pathogens. A systematic review by Goyet et al 39 looking at resistance patterns of CAP pathogens in Cambodia and neighbouring countries showed that up to 14% of S. pneumoniae and 26.5% of K. pneumoniae were resistant to amoxicillin-clavulanic acid. Streptococcus pneumoniae also displayed a high resistance to trimethoprim/sulfamethoxazole (average of 78.2%) and wide range of resistance patterns to cephalosporins: between 5.7% and 33.3% to ceftriaxone, and up to 47.4% to cefuroxime.…”
Section: Bacterial Pneumoniamentioning
confidence: 99%
See 1 more Smart Citation
“…38 This has changed the way local clinicians initiate their empiric treatment for patients admitted for severe CAP, with antibiotics deliberately chosen to cover Gram-negative organisms, melioidosis as well as Gram-positive pathogens. A systematic review by Goyet et al 39 looking at resistance patterns of CAP pathogens in Cambodia and neighbouring countries showed that up to 14% of S. pneumoniae and 26.5% of K. pneumoniae were resistant to amoxicillin-clavulanic acid. Streptococcus pneumoniae also displayed a high resistance to trimethoprim/sulfamethoxazole (average of 78.2%) and wide range of resistance patterns to cephalosporins: between 5.7% and 33.3% to ceftriaxone, and up to 47.4% to cefuroxime.…”
Section: Bacterial Pneumoniamentioning
confidence: 99%
“…As a result of this study, the authors have advocated the preservation of fluoroquinolones as they are not warranted as first-line therapy, and they are also used to treat TB, which importantly is endemic in this region. 39 This highlights the importance of continued surveillance of regional resistance patterns and revision of therapeutic guidelines.…”
Section: Bacterial Pneumoniamentioning
confidence: 99%
“…In the developing world, S. pneumoniae and H. influenzae, including type B, S. aureus, and enteric Gram negatives are causes of pneumonia [152][153][154]. In Africa, non-typhoidal Salmonella is an additional common etiology of bacteremic pneumonia, especially among human immunodeficiency virus infected children [155,156].…”
Section: Community Acquired Pneumoniamentioning
confidence: 99%
“…Antimicrobial resistance in bacteria that cause infectious diseases is a global problem, even if it varies from region to region depending upon the antibiotic pressure in that locality [11]. Bacteria isolated from HIV patients with pneumonia shows varying degree of antimicrobial resistance to common antimicrobials [12]. Since bacterial pneumonia in HIV patients is the common pulmonary complication.…”
Section: Introductionmentioning
confidence: 99%